0397 Impact of Behavioral Insomnia Treatments on Quality of Life in Post-Menopausal Women. (27th April 2018) - Tallent, G; Cheng, P; Fellman-Couture, C; Tonnu, C; Moss, K; Arnedt, T; Drake, C
Abstract: Introduction: Insomnia in post-menopausal women is commonly associated with reduced quality of life. Preliminary data suggest that both Cognitive Behavioral Therapy for Insomnia (CBT-I) and the Sleep Restriction Therapy component of CBTI (SRT) reduce insomnia severity in this population. While SRT is the shorter alternative to full CBTI in improving insomnia (2 versus 6 weeks), the differences in impact on quality of life in this population have not yet been investigated. Methods: 148 females (mean age=56.5, SD=5.61) with insomnia concurrent with menopause were randomized to one of three conditions: CBT-I (N=50), SRT (N=49), and Information-only Control (IC, N=49). Quality of life was measured using the Short Form Health Survey (SF-36; range=0–100), administered at baseline, immediately post-treatment, and at 6-month follow-up. Results: Repeated-measures ANOVA revealed that the CBT-I, SRT, and IC did not differ at baseline on any domains (p>.05) except for emotional role-limitations (p<.05). Results revealed significant group differences in change of energy over time, Group x Time, F(3.7, 212.4)=5.5, p<.0001. Energy increased in both the CBT-I and SRT conditions (CBT-I: F(1.9, 70.6)=22.7, p<.0001, SRT: F(1.7, 68.1)=13.4, p<.0001), while no differences were detected in the IC condition. Increases in energy at post treatment (CBT-I: 9.2 points, SRT: 8.6 points) were sustained after SRT but continued to improve following CBT-I. At 6-month follow-up, overall change in energy was 30% greater in the CBT-I (15.5 points) than the SRT condition (10.9 points). Based on SF-36 population norms of women in this age group, this change corresponds to an increase from the 30 th to the 57 th percentile in CBT-I and from the 28 th to the 52 nd percentile in SRT; women in IC did not improve beyond the 32 nd percentile. No other group differences were detected. Conclusion: Findings from this study demonstrate that both the full CBT-I and the shorter SRT option improve and normalize self-reported energy in post-menopausal women with concurrent insomnia. However, gains in energy following SRT may be less robust over time. Future study may determine how such gains relate to improvements in objectively-measured alertness in this population. Support (If Any): R01NR013959.